Quantum dots find their stride in single molecule tracking - Bruchez, Marcel P. (2011)
Thirteen years after the demonstration of quantum dots as biological imaging agents, and nine years after the initial commercial introduction of bioconjugated quantum dots, the brightness and photostability of the quantum dots has enabled a range of investigations using single molecule tracking. These materials are being routinely utilized by a number of groups to track the dynamics of single molecules in reconstituted biophysical systems and on living cells, and are especially powerful for investigations of single molecules over long timescales with short exposure times and high pointing accuracy. New approaches are emerging where the quantum dots are used as “hard-sphere” probes for intracellular compartments. Innovations in quantum dot surface modification are poised to substantially expand the utility of these materials.